2019
DOI: 10.1088/1741-2552/aafdd1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial localization of EEG electrodes using 3D scanning

Abstract: Objective. A reliable reconstruction of neural activity using high-density electroencephalography (EEG) requires an accurate spatial localization of EEG electrodes aligned to the structural magnetic resonance (MR) image of an individual’s head. Current technologies for electrode positioning, such as electromagnetic digitization, are yet characterized by non-negligible localization and co-registration errors. In this study, we propose an automated method for spatial localization of EEG electrodes using 3D scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
63
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 36 publications
9
63
0
2
Order By: Relevance
“…Both the structured-light and infrared 3D scanning methods were more reliable than digitizing with the ultrasound method. Furthermore, our reliability results for the two 3D scanners align well with a recent study that showed that an infrared 3D scan could automatically digitize electrode locations on three different EEG caps and achieve good reliability after additional post-processing [39]. Of the two 3D scanners we tested, the less expensive infrared 3D scanner was more reliable, had higher validity, and resulted in less dipole uncertainty, compared to the structured-light 3D scanner.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Both the structured-light and infrared 3D scanning methods were more reliable than digitizing with the ultrasound method. Furthermore, our reliability results for the two 3D scanners align well with a recent study that showed that an infrared 3D scan could automatically digitize electrode locations on three different EEG caps and achieve good reliability after additional post-processing [39]. Of the two 3D scanners we tested, the less expensive infrared 3D scanner was more reliable, had higher validity, and resulted in less dipole uncertainty, compared to the structured-light 3D scanner.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, common EEG analysis toolboxes such as EEGLAB [37] and FieldTrip [38] support using 3D scanners to digitize the electrode locations. Studies suggest that 3D scanners can improve digitization accuracy and significantly reduce digitization time [39]. Using other camerabased systems such as time-of-flight scanners and virtual reality headsets were also reported to provide comparable digitization reliability as the ultrasound or electromagnetic digitizing methods, while reducing the time spent for digitizing the EEG electrodes [27], [40], [41].…”
Section: Introductionmentioning
confidence: 99%
“…The GUI in SPOT3D enables the user to correct imprecisions in the spatial registration of the individual 3D scan to MR space, as well as in the identification of head marker positions. This enhances the positioning accuracy and the overall usability of the 3D scanning technique in comparison with our previous automated method 17 .…”
Section: Introductionmentioning
confidence: 81%
“…Thanks to the colour information and high resolution of the 3D scan, surface markers on the individual’s scalp can be localized with low positioning errors 4,16 . In our most recent work, we introduced an automated method for accurate spatial registration of a 3D scan to the structural MR image, as well as for detecting and labelling EEG sensors 17 .…”
Section: Introductionmentioning
confidence: 99%
“…For the individual geometrical description of the head (mesh), the anatomical image was segmented into 12 tissue classes (skin, eyes, muscle, fat, spongy bone, compact bone, cortical gray matter, cerebellar gray matter, cortical white matter, cerebellar white matter, cerebrospinal fluid and brain stem), based on the MIMA model [87] using SPM12 (http://www.fil.ion.ucl.ac.uk/spm/software/spm12/) as described previously [8890]. The EEG electrode positions were rigidly co-registered to the individual head surface (skin contour) by projecting the electrode coordinates in the native space through a rigid-body transformation, based on: (i) the estimation of anatomical landmarks (nasion, left/right peri-auricular points), (ii) the alignment of the electrode positions on the head surface through Iterative-Closest Point registration, and (iii) the projection of the electrodes onto the surface choosing the smallest Euclidean distance [91]. Conductivity values for each tissue class were grounded on previous findings [92, 93].…”
Section: Methodsmentioning
confidence: 99%